Kekuatan Pembuktian Pembatalan Perjanjian Pinjam Pakai Di Bawah Tangan Terkait Hak Guna Pakai Atas Tanah - Leny Agustan (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
One of the agreements that can be attached to land is a land loan agreement. Ownership of goods that are used as objects of loan, the provisions of Article 1741 of the Civil Code explain that, in a loan, the lender remains the owner of the loaned goods. Furthermore, Article 1742 of the Civil Code states that, anything that can be used by people and is not destroyed due to use, can be the subject of a loan agreement. In relation to the loan agreement, there was a case around 1991, a loan agreement was made for a plot of land measuring 1,500 m2 (one thousand five hundred square meters) which was used as an educational facility in the form of a public elementary school. Then, upon agreement of the parties, a Certificate of Land Use Rights was made. The lawsuit resulted in a Decision by the Cibinong District Court which declared the loan agreement and the certificate of use rights for a plot of land ownership that had been used for educational facilities null and void or had no legal force and decided that the object of the dispute should be returned to its owner in its original condition. The appeals court declared all letters or documents, as well as all agreements that referred to the object of the dispute, null and void. Based on the description, the problem arises regarding How is the evidentiary power of the cancellation of the land use agreement and the granting of land use rights? Based on the formulation of the problem, the objectives are as follows, to determine the evidentiary power of the cancellation of the land use agreement and the granting of land use rights? The research is explanatory, the source of library data, in the form of secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Based on the results of the research, it can be concluded that, the provisions of Article 1742 of the Civil Code explain that the object of the loan is everything that is not destroyed by use. Land is an object that cannot be destroyed by use, so that land can be used as an object of the loan agreement. Evidence in the form of private writings, if one of the parties or the heirs of one of the parties denies or does not acknowledge the writing, then the judge must order that the truth of the writing or signature be examined in court, if the signature of the letter which is a private deed is acknowledged but the contents of the private deed are denied then the value of the formal strength and retroactive evidence collapses and plummets. Therefore, the judge can consider canceling the private writings